Alternative tax-benefit strategies to support children in the European Union: Recent reforms in Austria, Spain and the UK - Horacio Levy; Christine Lietz; Holly Sutherland (Institute for Advanced Studies (IHS), 2006)
We compare three EU countries that have recently experienced substantial but very different reforms of their family support systems: Austria, Spain and the UK. The structure of these systems is different: Austria emphases universal benefits, Spain tax concessions and the UK means-tested benefits. First the paper compares the distributional implications of these three approaches. The recent reforms have reinforced existing structures while increasing the amount of spending for children. The second step is to ask: What would have happened if these countries had transformed the architecture of their systems in either of the other two directions? We use EUROMOD, the European tax-benefit microsimulation model that is designed for making cross-country comparisons and answering what if questions such as these. We find that the three factors that can be distinguished - the level of spending, its structure, and the way it impacts in a national context - are all important to varying degrees.
Keywords: C8; I3; 330; children; European Union; policy reform; microsimulation; Familienleistungsausgleich; EU-Staaten; Österreich; Spanien; Großbritannien